Effect of lyophilized aqueous leaf extract of Aquilaria subintegra on aphrodisiac properties in mice - Haniza Hanim Mohd Zain (Tanjong Malim, 2019)
Effect of lyophilized aqueous leaf extract of Aquilaria subintegra on aphrodisiac properties in mice by Haniza Hanim Mohd Zain